Reducing Total Dissolved Solid of Livestock Wastewater with Moringa Seed Powder - Merdana, I Made; Suada, I Ketut; Putra, I Putu Agus Santika (Advances in Tropical Biodiversity and Environmental Sciences; Vol 4 No 1 (2020): ATBESDO - 10.24843/ATBES.2020.v04.i01.p01, 2020)
In recent years environmental pollution has become a problem that needs attention because it causes negative impacts on ecosystems. The increase in cattle raising is directly proportional to livestock waste produced both from feces and excreted urine. Most people do not know how to process animal wastewater, so they dispose the livestock waste into water areas such as rivers that flow close to settlements. Water quality can be measured by several parameters, one of which is total dissolved solids (TDS). This parameter states the amount of solute both organic and inorganic in a solution. Moringa seeds have a coagulant effect due to their cationic electronic poly protein content. The purpose of this study was to determine the effect of moringa seeds on reducing TDS of livestock wastewater. The sample of this study was cattle farm wastewater taken from the cages of members of the Walung Mekar farmer group. Moringa seed powder concentrations used in this study were 50 mg/L, 100 mg/L and 150 mg/L. Observation was conducted in various time periods 0 minutes, 20 minutes, 40 minutes, 60 minutes. The TDS calculation method used gravimetric calculations (SNI 06-6989.27-2005). The results of variance indicated that Moringa oleifera powder had a very significant effect on the reduction of TDS levels in livestock wastewater. In summary, the best concentration of Moringa oleifera powder at 150 mg/L and the best deposition time at 60 minutes was able to reduce TDS levels.